Functional analysis of carpel developmental genes in California poppy (Eschscholzia californica) - Yellina, Aravinda Lakshmi; Justus Liebig University Giessen (My University, 2015)
The main objective of my study is to understand the functional evolution of novel morphologies in correlation with changes in the molecular genetic mechanisms over a period of time. One can understand the source for the existence of a wide diversity of forms by uncovering the developmental processes behind it. The plant evolutionary developmental biology (evo-devo) emerged as a branch of study that aims at unraveling the molecular and genetic mechanisms responsible for the origin and diversification of plant morphologies during the process of evolution. Flowering plants or angiosperms are the most dominating terrestrial plant ecosystems and flowers are the reproductive structures responsible for their successful adaptation. The flower comprises of four different floral organs as sepals, petals, stamens, and carpels. Variations in these organs have contributed considerably to the diversification of angiosperms. Moreover, the origin and diversification of the female reproductive organ, the carpel, was a major contributor for the evolutionary success of flowering plants. Therefore, the functional analysis of carpel developmental genes in phylogenetic informative species is one way of deciphering plant development in an evolutionary context.The molecular mechanisms governing carpel development have been studied intensively in the core eudicot model species Arabidopsis thaliana (Arabidopsis) and to some extent in the monocot model plant Oryza sativa (Rice). However, such studies are limited in other evolutionary lineages due to lack of genetically tractable model systems. To overcome this obstacle, the basal eudicot plant, Eschscholzia californica (California poppy) has been established as a versatile developmental model species based on its phylogenetic position and its amenability to genetic manipulation. Hence, the molecular genetics of carpel development in California poppy helps in bridging the evolutionary gap between monocots and higher eudicots. AGAMOUS (AG) is one of the important carpel developmental genes involved in specifying stamen and carpel identity in A. thaliana. In E. californica, there are two AG homologs, EScaAG1 and EScaAG2 which exhibit high sequence similarity at both nucleotide and protein levels. However, expression analyses through real-time qRT-PCR have shown that EScaAG2 is being expressed stronger in the inner stamen whorls and EScaAG1 transcripts are more abundant in the central carpels. Furthermore, downregulation of EScaAG1 through Virus-induced gene silencing (VIGS) resulted in the homeotic conversion of outer, peripheral whorls of stamens into petals and VIGS-EScaAG2 led to the homeotic transformation of inner and central whorls of stamens into petals. Additionally, functional analysis of both EScaAG genes through VIGS has resulted in the homeotic conversion of carpels into petal-like structures. According to the ABCE model of floral organ specification, petal identity requires the presence of the floral homeotic B function genes. The results of the present study have shown that the expression of a subset of B-function genes extends into the central fourth whorl when the C function is reduced. This suggests a phenomenon of B function gene regulation by the floral homeotic C function gene EScaAG2, a new functional domain of C class genes that has not been uncovered in any other model species.In the second project, Agrobacterium tumefaciens mediated stable genetic transformation was attempted for E. californica with a special emphasis on establishing a reproducible transgenic regeneration system. As a new source of explant tissue that was used as a starter culture, unripe seeds were selected and the protocol was optimized to produce embryogenic calli with efficient somatic embryogenesis and subsequent plant regeneration. The unripe seeds collected during a timeframe of 22-24 days after anthesis (DAA) proved to be suitable to induce callus production. Furthermore, the addition of sucrose in all the tissue culture growing media enhanced the efficiency of subsequent somatic embryogenesis, plantlet regeneration and root induction from the unripe seed sources.

Eines der wichtigsten Themen der biologischen Forschung ist es, die Entstehung und Entwicklung neuer Morphologien zu verstehen, die auch durch Änderungen der zu Grunde liegenden genetischen Netzwerke über evolutionäre Zeiträume entstehen. Diese Entwicklungsprozesse aufzudecken ist ein Weg, sich der Vielfalt biologischer Formen wissenschaftlich zu nähern. Der Forschungszweig der evolutionären Entwicklungsbiologie (Evo-Devo) versucht dabei, die molekularen und genetischen Mechanismen zu entschlüsseln, die für die Entstehung und Diversifizierung der Pflanzenmorphologie während des Prozesses der Evolution verantwortlich sind. Blütenpflanzen oder Angiospermen dominieren heute die Landökosysteme. Ihre Blüten sind reproduktive Strukturen und bestehen im Allgemeinen aus vier verschiedenen Organen, den Kelchblättern, Blütenblättern, Staubblättern und Fruchtblättern. Variationen in den Blütenstrukturen haben selbst viel zur Diversifizierung der Angiospermen beigetragen. Auch war die Entstehung und die Diversifizierung der Fruchtblätter und des daraus entstehenden Fruchtknotens ein wichtiger Faktor für den evolutionären Erfolg der Blütenpflanzen. Daher ist die funktionelle Analyse von Karpell-Entwicklungsgenen in phylogenetisch informativen Spezies ein vielversprechender Forschungsansatz, um die pflanzliche Entwicklung in einem evolutionären Kontext besser zu verstehen.Die Fruchtblatt-Entwicklung wurde intensiv in der höheren eudikotylen Modellpflanze Arabidopsis thaliana und dem monokotylen Getreide Oryza sativa untersucht. Ähnlich intensive Studien sind in solchen evolutionären Linien, die zwischen den höheren eudikotylen und den monokotylen Arten vermitteln, auf Grund fehlender Modellsysteme begrenzt. Aus diesem Grund wurde der basale eudikotyle Kalifornische Mohn, Eschscholzia californica, aufgrund seiner phylogenetischen Position und der Möglichkeit genetischer Manipulationen als ein vielversprechender Modelorganismus für Studien zur Karpell-Entwicklung etabliert. Diese Studien können dazu beitragen, die evolutionäre Entwicklung besser zu verstehen, die zwischen monokotylen und höheren eudikotylen Pflanzen stattgefunden hat.AGAMOUS (AG) ist das C-Klasse Gen, das die Identität der Staubblätter und Karpelle in A. thaliana bestimmt. In E. californica gibt es zwei AG Gene, EScaAG1 und EScaAG2, welche sowohl auf der Nukleotid-, als auch auf der Proteinebene eine hohe Ähnlichkeit aufweisen. Real-time qRT-PCR Experimente zeigen, dass EScaAG2 stärker in den Staubblättern exprimiert wird, während Transkripte von EScaAG1 stärker in den Karpellen nachweisbar sind. Der transiente knock-down von EScaAG1 via virus-induced gene silencing (VIGS) resultiert in der homeotischen Transformation der äußeren Staubblattwirtel in Blütenblätter, der von EScaAG2 in der Transformation der inneren Staubblattwirtel in Blütenblätter. Die funktionelle Analyse beider EScaAG Gene zusammen durch VIGS führt zu homeotischer Transformation aller Staubblätter in Blütenblätter, sowie der Karpelle in Blütenblatt-ähnliche Strukturen. Die Blütenblatt Identität erfordert dabei das Vorhandensein der floralen homeotischen B-Klasse Gene. Die dargestellten Ergebnisse zeigen, dass die Expression eines Teils der B Funktion in den zentralen Wirtel hinein erweitert wird, wenn die Expression der C-Funktion reduziert wird. Diese Ergebnisse lassen eine funktionelle Domäne der C-Klasse Gene in der Regulation von B-Klasse Genen erkennen, die bisher noch nicht bei anderen Modellorganismen entdeckt wurde.In einem weiteren Projekt wurde mit Hilfe der Agrobacterium tumefaciens-vermittelten stabilen genetischen Transformation ein weniger transienter Ansatz zur Erstellung transgener Pflanzen, mit einem Schwerpunkt auf die Optimierung des Regenerationssystems, etabliert. Hierbei wurden unreife Samen als die optimalen Explantate etabliert und dahingehend optimiert, embryogene Kalli mit effizienter somatischer Embryogenese und Regeneration zu produzieren. Die unreifen Samen, welche während eines Zeitraums von 22- 24 DAA gesammelt wurden, zeigten sich als optimal geeignet, eine ausreichende Kallus Produktion zu induzieren. Die Zugabe von Saccharose in alle Wachstumsmedien der Gewebekulturen verbesserte weiterhin die Effizienz der somatischen Embryogenese, die Plantlet-Regeneration sowie die Wurzelinduktion aus den Explantaten unreifer Samen.
Funktionelle Analyse von Karpel Entwicklungsgenen im Kalifornischen Mohn (Eschscholzia californica)
Keywords: ddc:580